Total Parenteral Nutrition Treatment Improves the Nutrition Status of Gynecological Cancer Patients by Improving Serum Albumin Level - Yan, Xin; Zhang, Sanyuan; Jia, Junmei; Yang, Jiaolin; Song, Yilai; Duan, Haoran (Frontiers in Medicine, 2022)
Background Malnutrition is often observed in gynecological cancer patients, however its prevalence in these patients remains largely unexplored. Total parenteral nutrition (TPN) is a nutritional intervention method that has controversial treatment outcome on gynecological cancer patients. The present retrospective study is designed to evaluate the nutrition status and TPN treatment outcome on patients diagnosed with endometrial, cervical or ovarian malignant tumors. Methods Medical records of a total of 263 patients treated at the First Hospital of Shanxi Medical University, China were included. Nutrition status was assessed by patient-generated subjective global assessment (PG-SGA). Patients were grouped based on nutrition status, cancer type or treatment strategy for clinical characteristic comparison. Multivariable logistic regression analysis was used to identify predictors for malnutrition status and hospital stay duration. Results Presence of endometrial and cervical cancer, body weight before nutritional intervention and serum albumin level (P < 0.001 for all) were found to be significant predictors for malnutrition status in gynecological cancer patients. In the malnourished patients, those who were treated with TPN had significantly lower serum albumin levels before and after treatment (P < 0.001) and PG-SGA scores after treatment. Also, TPN treatment could significantly increase the serum albumin levels in these patients after 1 week. In addition, shorter hospitalization period was needed for TPN-treated endometrial (P = 0.019) and ovarian (P < 0.001) patients. Moreover, serum albumin levels (P < 0.001), use of TPN treatment (P = 0.025) and nutrition status (P = 0.010) were identified to be independent predictors for hospital stay duration. Conclusion Our results suggest that malnutrition is a significant clinical manifestation in gynecological cancer patients who may benefit from TPN treatment for reduced hospitalization and improved serum albumin levels.